2018
DOI: 10.1016/j.jana.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antiretroviral Stock-Outs on Medication Adherence Among Patients Living With HIV in Ghana: A Qualitative Study

Abstract: Stock-outs of medications for antiretroviral therapy have been reported as a significant barrier to HIV care in sub-Saharan Africa, but patient responses to these shortages have not been fully described. The aim of our study was to employ qualitative methods to examine the role of medication stock-outs in contributing to treatment interruption among a sample of patients already engaged in care for HIV at Komfo Anokye Teaching Hospital in Kumasi, Ghana. We found that medication stock-outs presented a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
1
12
0
1
Order By: Relevance
“…Our review search was conducted on 9 December 2016 and it is possible that some of the landscape regarding stigma and access to care may have changed in the ‘test and treat’ and differentiated service delivery era. However, after conducting an updated search and rapidly appraising recently published studies (up till 1 August 2018), we identified several studies which supported our findings, specifically regarding quality of health services [130133], disrespectful health workers and the role of power in health service delivery [132, 134], lack of access to health services [130, 131], competing priorities and unpredictable life circumstances [135138], the role of the social world [131, 132, 139], influence of gender roles [140], medical pluralism [132, 141], the motivating influence of having dependents [142, 143], the challenges of same day ART initiation[144], the barriers to care caused by stigma [130, 131, 138, 143, 145, 146], challenges to accessing care for PWD [147], the benefits of support [131, 132, 148, 149], and fluctuations in engagement over time [131]. We therefore feel that the findings of this review remain relevant to current HIV populations.…”
Section: Discussionsupporting
confidence: 65%
“…Our review search was conducted on 9 December 2016 and it is possible that some of the landscape regarding stigma and access to care may have changed in the ‘test and treat’ and differentiated service delivery era. However, after conducting an updated search and rapidly appraising recently published studies (up till 1 August 2018), we identified several studies which supported our findings, specifically regarding quality of health services [130133], disrespectful health workers and the role of power in health service delivery [132, 134], lack of access to health services [130, 131], competing priorities and unpredictable life circumstances [135138], the role of the social world [131, 132, 139], influence of gender roles [140], medical pluralism [132, 141], the motivating influence of having dependents [142, 143], the challenges of same day ART initiation[144], the barriers to care caused by stigma [130, 131, 138, 143, 145, 146], challenges to accessing care for PWD [147], the benefits of support [131, 132, 148, 149], and fluctuations in engagement over time [131]. We therefore feel that the findings of this review remain relevant to current HIV populations.…”
Section: Discussionsupporting
confidence: 65%
“…The patient may weigh the value (i.e., attending the club and continuing to receive the benefit and convenience of club-based care) with the cost (i.e., loss of a day’s worth of wages), and decide that, although more time-consuming, receiving clinic-based standard care is ultimately more flexible, given the unpredictability of work opportunities. Typically, within the routine clinic-based standard of care, there is little downside to skipping a clinic appointment (if such appointment systems even exist), and many experienced ART patients may maintain a stockpile of medication to bridge short-term gaps [13]. Other models of differentiated care such as ART delivered in vending machines or at fast-track pharmacy queues may offer less stringent rules and thus more flexibility for some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Where drought and co-morbidities interact with economic stress, social vulnerabilities, medication stock-out, pills burden or side-effects from ART regimens, this can be detrimental for adherence. 2838,116,125…”
Section: Results: a Systems Understanding Of The Sensitivity Of Art Amentioning
confidence: 99%